Critical analysis of the enviromental assessment reports for the plantation projects in Sg Teru catchment - Chong, Li Chiun (Universiti Malaysia Sarawak (UNIMAS), 2005)
Loagan Bunut, the largest natural lake in Sarawak, is located on the flood plain of Batang Tinjar-Sungai Teru confluence in the Miri Division, Sarawak. Rapid change of land use in the upper catchment of Sg Teru had caused severe soil erosion and sedimentation problems in this river. The flood flows of Sg Teru carry sediment from the upstream of Sg Teru into the lake via Sg Bunut, causing rapid sedimentation and possible risk of complete disappearance of the LBNP Lake. Since the middle of 1990s, there are seven oil palm plantations developed within the catchment of Sg Teru and some adverse impacts had been identified as the consequences of the plantation activities. Environmental Impact Assessments (EIA) or Environmental Management Plan (EMP) studies were conducted for the seven plantation projects within the Sg Teru catchment. These EIA or EMP reports were submitted to the Natural Resources and Environment Board (NREB), Sarawak and all of them were approved on the premise that the adverse impacts predicted in the environmental studies can be well controlled or mitigated. However, adverse impacts originated from the plantation development activities persist. This dissertation critically analyzes the coverage and quality of the seven EIA reports for the oil palm plantations within the catchment of Sg Teru. The study has focused on the reports of environmental assessment (EA) of six oil palm plantations and one forest plantation located within the catchment of Sg Teru, upstream of LBNP. The mitigation measures and residual impacts of the plantation projects addressed in the EA reports were reviewed for their coverage and adequacies and comments were given. One of the main environmental issues of the plantation project is soil erosion and siltation of the neighbouring water systems. Generally speaking, all the environmental assessment reports covered in this study had discussed the environmental issues of the plantation developments in a very general way. None of the reports addressed the issue of sedimentation and threats of pollution to the LBNP downstream of the plantations. These reports were found as not specific enough to their respective project areas. Nevertheless, most of the on-site impacts had been identified and assessed.